Istanbul and Crete in the Mid-1600s: Evliya Çelebi's Discourse on Orthodox Christians. (November 2019) - Faroqhi, Suraiya
The subject of our discussion is the travelogue of Evliya Çelebi, born in 1611 to a goldsmith of the sultans' palace known as Derviş Mehemmed Zılli and who probably died in Cairo around 1685. It is intriguing for a multitude of reasons, one of them especially relevant for the present purpose: While Evliya's work covers the entire Ottoman Empire and adjacent territories in ten substantial volumes, we do not know the patrons and/or other addressees that the author may have envisaged. While the author often mentioned two grand viziers and other figures of the highest levels of the Ottoman elite, who employed him and with whom he had good relations, by the mid-1680s they had mostly predeceased him, sometimes by several decades.